2021
DOI: 10.21203/rs.3.rs-923215/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering resistance to Zymoseptoria tritici in the Tunisian durum wheat landrace accession ‘Agili39’

Abstract: Background Septoria tritici blotch (STB), caused by Zymoseptoria tritici (Z. tritici), is an important biotic threat to durum wheat in the entire Mediterranean Basin. Although most durum wheat cultivars are susceptible to Z. tritici, research in STB resistance in durum wheat has been limited. Results In our study, we have identified resistance to a wide array of Z. tritici isolates in the Tunisian durum wheat landrace accession ‘Agili39’. Subsequently, a recombinant inbred population was developed and tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…In this study, the four identified MSR-QTLs are likely to provide resources for the development of Z. tritici resistant cultivars both in Australia and globally. In comparison to previously published studies, our detected MSR-QTL QStb.wai.1B.1 was co-located with QStb.cim-1BS (Dreisigacker et al 2015), and the locus of QStb.wai.2B.1 co-located with QTL-2BL and Qstb2B_1 (Aouini 2018; Ferjaoui et al 2021) and the major gene Stb9 (Chartrain et al 2009). While the locus of QStb.wai.5A.1 co-located with QStb.cim-5AL-2 (Dreisigacker et al 2015) and QStb.B22-5A.a (Naz et al 2015).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In this study, the four identified MSR-QTLs are likely to provide resources for the development of Z. tritici resistant cultivars both in Australia and globally. In comparison to previously published studies, our detected MSR-QTL QStb.wai.1B.1 was co-located with QStb.cim-1BS (Dreisigacker et al 2015), and the locus of QStb.wai.2B.1 co-located with QTL-2BL and Qstb2B_1 (Aouini 2018; Ferjaoui et al 2021) and the major gene Stb9 (Chartrain et al 2009). While the locus of QStb.wai.5A.1 co-located with QStb.cim-5AL-2 (Dreisigacker et al 2015) and QStb.B22-5A.a (Naz et al 2015).…”
Section: Discussioncontrasting
confidence: 53%
“…Further, the QTLs, QTL-2BL and Qstb2B_1 were also mapped from the durum wheat ‘Agili 39’and are reported to be responsible for Z. tritici resistance at both seedling stage and adult-plant stage using multiple isolates. It has also been suggested that this locus could be the major gene Stb9 (Aouini 2018; Ferjaoui et al 2021).…”
Section: Discussionmentioning
confidence: 99%